EFFECT OF DDT ON THE HISTOLOGY OF CORPORA CARDIACA (CC) OF THE ADULT MALE AK GRASSHOPPER POEKILOCERUS PICTUS (ORTHOPTERA : ACRIDIAE) AT DIFFERENT TEMPERATURES. - SINGH, S.C.; KHAN, T.R.; PANDEY, N.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
The corpora cardiaca (cc) showed degenerations and reductions in their cell size and nuclei after DDT treatment at different temperatures (32 ± 20 C and 15° C). The disruptive effects of DDT treatment was more pronounced at 15°C than at 32 ± 2°C. The cytoplasm of chromophil and chromophobe cells of corpora cardiaca (cc) became vaculated due to the effect of DDT.